Efficiency of DECA on ship emission and urban air quality: A case study of China port. (15th August 2022) - Yang, Lei; Zhang, Qijun; Lv, Zongyan; Zhang, Yanjie; Yang, Zhiwen; Fu, Fei; Lv, Jianhua; Wu, Lin; Mao, Hongjun
Abstract: As the largest container port in northern China, the prosperous maritime trade has not only promoted the economic development of Qingdao port but also brought serious pollution to the air quality. Ship emissions have caused a significant influence on public health. The establishment of the Domestic Emission Control Area (DECA) is a key policy to reduce ship emissions in recent years. It has been implemented in Qingdao Port from January 1, 2019. To evaluate the environmental benefits of the DECA policy, this study established a bottom-up ship emission inventory in 2020 for Qingdao based on Automatic Identification System (AIS) data. Changes in ship emissions and their impact on air quality in Qingdao are evaluated for the same study area before and after the implementation of DECA policy. The total emissions in all study area for SO2, NOX, PM10, PM2.5, HC and CO in 2020 are 8.16 × 10 3, 3.31 × 10 4, 1.25 × 10 3, 1.15 × 10 3, 1.18 × 10 3, 2.15 × 10 3 tons (t), respectively, reductions of 67.9%, 15.4%, 63.2%, 62.9%, 27.2% and 23.2% compared with 2016, and reductions of 73.42%, 29.97%, 69.54%, 69.26%, 39.71%, 36.44% compared with the scenario without DECA in 2020. The inter-month change and spatial distribution of ship emissions are similar in both years. Shinan District, Shibei District and Huangdao District are most affected by ship emissions, with the largest influence in summer. The ship's contribution to air pollution in each area had been significantly reduced, especially for SO2 and PM after DECA policy. However, the emission reduction of other pollutants is limited, so it is necessary to further enhance the DECA policy. Our research aims to conduct a comprehensive assessment of the environmental benefits for DECA policy, and provide support for the further improvement of the subsequent measures. Graphical abstract: Image 1 Highlights: High spatiotemporal resolution ship emission inventory for Qingdao in 2020 is updated. Total ship emission in Qingdao during 2020 was 46, 965.7 tons, 37.7% lower than 2016. More than 50% of ship pollutants occur within the baseline of territorial sea. Ship emissions in summer have the most significant impact on urban air quality. DECA policy has reduced ship emission of SO2 by 73.4% and PM2.5 by 69.5%.